PEMBERDAYAAN EKONOMI KREATIF BERBASIS KEARIFAN LOKAL "SINGKONG" GUNA MENUNJANG INCOME KELUARGA DALAM PEMENUHAN GIZI IBU HAMIL, BAYI/BALITA DI DESA PASIRAWI, PANDEGLANG, BANTEN - Siti Rusyanti; Yayah Rokayah; Omo Sutomo (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Maternal and Child Health (MCH) is closely related to family nutritional intake, which is strongly influenced by economic conditions. Pasirawi Village, Banjar District, Pandeglang Regency, Banten Province, is one of the villages experiencing stunting problems, with four toddlers identified as stunted. One of the contributing factors is limited family income. Therefore, community empowerment is required to address existing stunting cases and prevent further increases. Pasirawi Village has abundant natural resources that support community-based agriculture. One of its main commodities is cassava (manioc), a high-quality crop that is sold at a relatively low price of Rp 2,000–3,000 per kilogram. This price is insufficient to serve as a stable primary income for families. To increase its economic value, the development of a creative economy based on local wisdom is necessary. Many community members, especially women, have initiated home industries producing Opak Singkong, a traditional cassava-based cracker enjoyed by all age groups. Currently, production is carried out manually, starting from pounding boiled cassava, adding spices, molding, drying, and marketing the product as raw opak. Situation analysis identified challenges in production efficiency and marketing, particularly in product packaging. This community service program provides stimulants in the form of production equipment and training on creative economic development, including improved packaging techniques. The expected outcomes include increased production capacity, wider market reach, improved family income, and better fulfillment of family nutritional needs, ultimately supporting improved maternal and child health. This initiative strengthens resilience through collaboration, sustainability, education, innovation, inclusivity, and long-term impact.